Work addiction, workplace stress, and burnout syndrome among teachers in the Armed Forces Academies Preparatory School - Nithivasin, Sunansa; Kalayasiri, Rasmon (Chulalongkorn Medical Journal, 2021)
Background: Teachers have many aspects roles of responsibilities which consume more time than usual and could lead to work addiction and burnout syndrome. However, there has never been any study on work addiction and burnout syndrome among teachers in Thailand in order to raise awareness and seek for prevention measures of these work addiction and burnout of teachers in the future. Objective: The purpose of this study was to determine the prevalence and associated factors of work addiction and burnout syndrome in teachers. Methods: This cross-sectional descriptive study was conducted by 113 teachers of the Armed Forces Academies Preparatory School by using Thai version of questionnaires about demographic data, work-related data, Thai job content questionnaires (Thai JCQ), bergen work addiction scale (BWAS), and Thai Version of Maslach Burnout Inventory (Thai MBI). The statistical analysis were frequency, percentage, mean, standard deviation, median and logistic regression. Results: The study found that the prevalence of work addiction and burnout syndrome among the teachers in the Armed Forces Academies Preparatory School was 11.5% and 30.1%, consecutively. The factors affecting work addiction included psychological job demand, while personal factors and work-related factors did not affect work addiction. The study also found that the factors affecting burnout syndrome was job control and job security. Conclusion: The study inferred that the prevalence of work addiction was not as high as one found in the previous study partly because of different groups of studied population and questionnaires and the teachers did well on time management. On the other hand, the prevalence of burnout syndrome was fairly high. Nevertheless, screening and searching people who are potentially at risk may help prevent them from work addiction and burnout syndrome and may also help pave ways for taking care of those with the conditions.